The development and application of molecular markers for linkage mapping and quantitative trait loci analysis of important agronomic traits in oil palm (Elaeis guineensis Jacq.) - Gan, Siou Ting (2014)
Oil palm (Elaeis guineensis) produces over five times more oil/year/hectare than oil seed rape and accounted for 33% of world vegetable oil production in 2011. Being a cross-pollinated perennial tree crop with long breeding cycles (typically 12 years) and a large planting area requirement (usually 143 palms/hectare), utilization of molecular technology could greatly improve the efficiency of oil palm breeding. In the present study, various approaches were used to develop molecular markers for genetic linkage mapping and QTL analysis, with the ultimate goal of marker-assisted selection in oil palm.